A Study of Autonomous Learning Strategies Implemented by Members of Indonesia English Community - Henry Reggy Leo Capital; Yuliyanto Sabat (ITScience (Information Technology and Science), 2023)
Autonomous learning is extremely important because it helps students promote independency, self-awareness, determination, and adaptability in technology employment in learning. The aim of this study is to describe the learning strategies of each autonomous learning level among members of the English Conversation club and to inquire about their outcomes in the form of speaking fluency. Therefore, this study case study research design to find patterns and connections, and inquire phenomena in depth. The results show that the advanced and intermediated level participants employ a metacognitive strategy which helped them to plan, monitor, and evaluate their learning, additionally, they displayed a high level of speaking fluency as the outcome of the strategy they employed. The beginner level employed a social mediation learning strategy and showed less autonomous learning activity but still had high speaking fluency, probably due the language aptitude. Whereas the emerging level participant employ a social mediation learning strategy and showed less autonomous activity, he displayed a low level of fluency. Participants with advanced, intermediated, and beginner level possess intrinsic motivation which helps them with their consistency and improvement. This study helps to understand the relationship between autonomous learning strategies, autonomous level, and speaking fluency outside of the classroom. It provides evidence that metacognitive strategy can lead to speaking fluency improvement and intrinsic motivation. Educators should develop teaching methods that promote the development of independent learning skills and intrinsic motivation in students.